Patients assisted by the palliative care center in a university hospital (Research, Society and Development, 2023)
Objective: The present study aimed to evaluate the clinical and epidemiological profile of patients referred to the palliative care service of a university hospital. Methods: A retrospective cohort study involved 138 patients in need of palliative care, aged between 4 months and 95 years, hospitalized from January 2020 to August 2021. Demographic, clinical, biochemical, radiological data and results were collected from medical records of patients. Results: According to the data analyzed during hospitalization, the average age is 65.89 years, with about 3 diagnoses or different clinical conditions. The most prevalent comorbidities were systemic arterial hypertension (82.61%) followed by neoplasms (79.71%). As for the outcome, most admitted patients died during hospitalization (71.54%). The time between hospital admission and admission to palliative care was shorter among cancer patients. A longer hospital stay and admission to palliative care was observed among patients with higher initial investments by the medical team. Conclusion: Palliative care is still mistakenly seen as end-of-life care. Detailed patient assessment and knowledge of the characteristics of patients who should be referred to palliative care help in the development of strategies to improve the service. The present study seeks to contribute to the modification of the end-of-life palliative care assistance profile.